Salt stress responses in pear and quince: physiological and molecular aspects - Serra, Sara <1979> (Alma Mater Studiorum - Università di Bologna, 2009)
The productivity of agricultural crops is seriously limited by salinity. This problem is rapidly increasing, particularly in irrigated lands. Like almost all the fruit tree species, Pyrus communis is generally considered a salt sensitive species, but only little information is available on its behavior under saline conditions. Previous studies, carried out in the Department of Fruit Tree and Woody Plant Science (University of Bologna), focused their attention on pear and quince salt stress responses to understand which rootstock would be the most suitable for pear in order to tolerate a salt stress condition. It has been reported that pear and quince have different ability in the uptake, translocation and accumulation of chloride (Cl-) and sodium (Na+) ions, when plants were irrigated for one season with saline water (5 dS/m). The aim of the present work was to deepen these aspects and investigate salt stress responses in pear and quince. Two different experiments have been performed: a “short-term” trial in a growth chamber and a “long-term” experiment in the open field. In the short-term experiment, three different genotypes usually adopted as pear rootstocks (MC, BA29 and Farold®40) and the pear variety Abbé Fétel own rooted have been compared under salt stress conditions. The trial was performed in a hydroponic culture system, applying a 90 mM NaCl stress to half of the plants, after five weeks of normal growth in Hoagland’s solution. During the three-weeks of salt stress treatment, physiological, mineral and molecular analyses were performed in order to monitor, for each genotype, the development of the salt stress responses in comparison with the corresponding “unstressed” plants. Farold®40 and Abbé Fétel own rooted showed the onset of leaf necrosis, due to salt toxicity, one week before quinces. Moreover, quinces displayed a significant delay in premature senescence of old leaves, while pears emerged for their ability to regenerate new leaves from apparently dead foliage with the salt stress still running. Physiological measurements, such as shoots length, chlorophyll (Chl) content, and photosynthesis, have been carried out and revealed that pears exhibited a significant reduction in water content and a wilting aspect, while for quinces a decrease in Chl content and a growth slowdown were observed. At the end of the trial, all plants were collected and organs separated for dry weight estimation and mineral analyses (Cu, Fe, Mn, Zn Mg, Ca, K, Na and Cl). Mineral contents have been affected by salinity; same macro/micro nutrients were altered in some organs or relocated within the plant. This plant response could have partially contributed to face the salt stress. Leaves and roots have been harvested for molecular analyses at four different times during stress conditions. Molecular analyses consisted of the gene expression study of three main ion transporters, well known in Arabidopsis thaliana as salt-tolerance determinants in the “SOS” pathway: NHX1 (tonoplast Na+/H+ antiporter), SOS1 (plasmalemma Na+/H+ antiporter) and HKT1 (K+ high-affinity and Na+ low-affinity transporter). These studies showed that two quince rootstocks adopted different responsive mechanisms to NaCl stress. BA29 increased its Na+ sequestration activity into leaf vacuoles, while MC enhanced temporarily the same ability, but in roots. Farold®40, instead, exhibited increases in SOS1 and HKT1 expression mainly at leaf level in the attempt to retrieve Na+ from xylem, while Abbé Fétel differently altered the expression of these genes in roots. Finally, each genotype showed a peculiar response to salt stress that was the sum of its ability in Na+ exclusion, osmotic tolerance and tissue tolerance. In the long-term experiment, potted trees of the pear variety Abbé Fétel grafted on different rootstocks (MC, BA29 and Farold®40), or own rooted and also rootstocks only were subjected to a salt stress through saline water irrigation with an electrical conductivity of 5 dS/m for two years. The purposes of this study were to evaluate salinity effects on physiological (shoot length, number of buds, photosynthesis, etc.) and yield parameters of cultivar Abbé Fétel in the different combinations and to determine the salt amount that pear is able to tolerate over the years. With this work, we confirmed the previous hypothesis that pear, despite being classified as a salt-sensitive fruit tree, can be cultivated for two years under saline water irrigation, without showing any salt toxicity symptoms or severe drawbacks on plant development and production. Among different combinations, Abbé Fétel grafted on MC resulted interesting for its peculiar behaviors under salt stress conditions. In the near future, further investigations on physiological and molecular aspects will be necessary to enrich and broaden the knowledge of salt stress responses in pear.